X-Chromosome Inactivation in Rett Syndrome Human Induced Pluripotent Stem Cells - Cheung, Aaron Y.; Horvath, Lindsay M.; Carrel, Laura; Ellis, James (Frontiers in Psychiatry, 2012)
Rett Syndrome (RTT) is a neurodevelopmental disorder that affects girls due primarily to heterozygous mutations in the X-linked gene encoding methyl-CpG binding protein 2 (MECP2). Random X-chromosome inactivation (XCI) results in cellular mosaicism in which some cells express wild-type MECP2 while other cells express mutant MECP2. The generation of patient-specific human induced Pluripotent Stem cells (hiPSCs) facilitates the production of RTT-hiPSC-derived neurons in vitro to investigate disease mechanisms and identify novel drug treatments. The generation of RTT-hiPSCs has been reported by many laboratories, however, the XCI status of RTT-hiPSCs has been inconsistent. Some report RTT-hiPSCs retain the inactive X-chromosome (post-XCI) of the founder somatic cell allowing isogenic RTT-hiPSCs that express only the wild-type or mutant MECP2 allele to be isolated from the same patient. Post-XCI RTT-hiPSCs-derived neurons retain this allele-specific expression pattern of wild-type or mutant MECP2. Conversely, others report RTT-hiPSCs in which the inactive X-chromosome of the founder somatic cell reactivates (pre-XCI) upon reprogramming into RTT-hiPSCs. Pre-XCI RTT-hiPSC-derived neurons exhibit random XCI resulting in cellular mosaicism with respect to wild-type and mutant MECP2 expression. Here we review and attempt to interpret the inconsistencies in XCI status of RTT-hiPSCs generated to date by comparison to other pluripotent systems in vitro and in vivo and the methods used to analyze XCI. Finally, we discuss the relative strengths and weaknesses of post- and pre-XCI hiPSCs in the context of RTT, and other X-linked and autosomal disorders for translational medicine.